Clinical features in a man with primary synovial sarcoma of the spermatic cord - Wang, Gong-Cheng; Li, Xue-Qin; Wang, Yun-Yan; Guo, Zhong-Ying; Hou, Pei-Jin (Asian journal of andrology, 2015)
Dear Editor, Synovial sarcoma （SS） is a rare malignant neoplasm in young adults？ It commonly arises around the major joints or tendon sheaths. Furthermore, it has been described in numerous locations unrelated to joint structures, such as the heart, kidney, prostate, etc., which may lead to a diagnosis pitfall. Here, we present an extremely rare case of primary SS originating in the spermatic cord.